Methods, Algorithms, and Means of Remote Long-Term Monitoring of the Security and Safety of People and their Property - Shevchuk, B. M. (Cybernetics and systems analysis, 2025)
The methodological and algorithmic foundations for the operation of terminal, local-regional, and global wireless networks for long-term monitoring of the security and safety of large groups of people and their property are proposed. Taking into account the operation of portable object systems of the monitoring network with many constraints, the prompt processing and encoding of samples of monitoring signals and video data frames are proposed. The encoding of the input monitoring data from transmitters, sensors, and video modules is based on the signal approach. According to this approach, the processing resources of object systems during the filtering and compression of monitoring signals and images ensure accurate encoding, decoding, and restoration of the parameters of the most informative signal readings and video signal pixels, which include extrema and inflection points of envelope signals and video signals. It is proposed to protect monitoring data arrays in the process of data compression and protection using one-time ciphers. The construction of energy-efficient and highly informative portable object systems for long-term monitoring of residents of cities and villages, operators of human-machine systems and complexes, personal and real property is considered.